Apuntes para el asesoramiento de la tesis universitaria - Campos Arenas, Agustín (2016)
The Thesis advice is a profesor responsability that must be assumed with the formal and disciplinary knowledge in order that the thesis preparation can be achieved. This article presents the common errors during this process, the formal basic knowledge about the dissertation adopted by the institution and concludes with somelines about the advisor.